Assessment of Red Sea Shoreline Dynamics Through Satellite Imagery and GIS Analysis - Abdel Aziz, Khaled Mahmoud (Salehan Institute of Higher Education, 2026)
Monitoring and analyzing coastal dynamics is essential due to continuous shoreline changes driven by natural processes and human activities with significant environmental and economic impacts. This study aims to quantitatively assess shoreline change along the Red Sea coast using integrated remote sensing and Geographic Information Systems (GIS) techniques. Multi-temporal satellite imagery from 1980 to 2025 was processed to extract shoreline positions, and shoreline change rates were calculated using the EPR method to determine patterns of erosion and accretion. The study area extends along the northwestern part of Saudi Arabia within the Tabuk region, covering Wadi al Ayn, NEOM Port, and the villages of Al Muwaylih, As Sawrah, Sharma, Al Khuraybah, and Qiyal. The results reveal that erosion rates exceed accretion rates across most shoreline segments during the study period. The average EPR of accretion reached 1.13 m/yr, while erosion recorded a higher magnitude with an average rate of −1.99 m/yr. Spatial analysis showed a total accretion area of 1.634 km² compared to a substantially larger erosion area of 19.624 km². This study lies in providing a comprehensive, long-term spatiotemporal assessment of shoreline dynamics using consistent satellite-based measurements, contributing updated baseline data for coastal management and sustainable development planning in the Red Sea region.